A Google, o sistema de media e a agregação de informação - Cádima, Francisco Rui (2018)
The complexity of the convergence model between traditional media and new media passes through a time of testing around the confrontation that has been observed between Google and the publishers of the press. Our goal is to resolve some issues that have been divisive for the current model of migration to digital, namely: interconnected economy versus traditional system of intellectual property; intermediation systems of access to information (engines, aggregators, social media) versus websites of traditional media. The solution that will be found for this litigation, probably does not resolve another issue which is of no less importance since it integrates the technical and algorithmic device of the new digital intermediaries: the conditioning of the news and therefore pluralism and diversity of information. A complexidade do modelo de convergência entre os media tradicionais e osnovos media passa por um tempo de provação em torno do confronto que setem verificado entre a Google e os editores de imprensa. A proposta é dirimiralgumas questões que têm sido fracturantes para o actual modelo de migraçãopara o digital, a saber: economia interconectada versus sistema tradicional depropriedade intelectual; sistemas de intermediação do acesso à informação (motores,agregadores, social media) versus sites de notícias dos media tradicional. Asolução que se venha a encontrar para este contencioso poderá, no entanto, nãoresolver uma outra questão que não é de menor relevância e que integra o dispositivotécnico e algorítmico dos novos intermediários digitais: o condicionamentoda matéria noticiosa e, portanto, do pluralismo e diversidade da informação.